The demand for money market mutual funds - Karlo Kauko (Bank of Finland, 2005)
This paper presents a model on the demand for money market funds (MMFs).These funds are a very close substitute for M1 deposits, except that MMFs do not satisfy immediate transaction requirements. The demand for MMFs strengthens when the intended volume of transactions is low.A high interest rate level makes it expensive to hold M1 deposits.High interest rate volatility, paradoxically, increases the risk of holding M1 deposits stronger than the risk of holding MMFs.The results are largely corroborated by Finnish data.
URN:NBN:fi:bof-20140807218
Keywords: G23; G29; E41; 330; money market mutual funds; money demand